Why the Bolsheviks won. - Stone, Norman (TLS. Times Literary Supplement, 1990)
Reviews several books about the Russian civil war. "Red Victory: A History of the Russian Civil War," by W. Bruce Lincoln; "Die Lage der Bauern in Russland 1880-1905 Sankt Katharinen: Scripta Mercaturae," by Heinz-Dietrich Lowe; "Party, State, and Society in the Russian Civil War: Explorations in Social History," edited by Diane P. Koenker, William G. Rosenberg and Ronald Grigor Suny.